Composition for forming heat insulating layer and heat insulating member

The composition of a binder resin, hollow particles, and water, with specific content ranges, addresses the challenges of peelability, dryness, and heat insulating properties in existing heat insulating layer compositions, resulting in a layer that is easy to apply and remove while providing effective thermal insulation.

JP7653230B2Active Publication Date: 2025-03-28ETEC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020132854
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-05
Publication Date
2025-03-28
Estimated Expiration
2040-08-05

AI Technical Summary

Technical Problem

Existing compositions for forming heat insulating layers on building materials, such as aluminum sashes, lack excellent peelability, dryness, and heat insulating properties, making them difficult to apply and remove efficiently.

Method used

A composition for forming a heat insulating layer containing a binder resin, hollow particles, and water, with hollow particle content between 30% to 75% and water content of 30% or less, which forms a heat insulating layer with improved peelability, dryness, and heat insulating properties.

Benefits of technology

The composition enables the formation of a heat insulating layer with excellent peelability, dryability, and heat insulating properties, facilitating easy application and removal, while maintaining effective thermal insulation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653230000001
    Figure 0007653230000001
Patent Text Reader

Abstract

To provide a heat insulation layer-forming composition capable of forming a heat insulation layer excellent in peelability, dryability and heat insulation, and to provide a heat insulation member.SOLUTION: The heat insulation layer-forming composition contains a binder resin, hollow particles, and water. The content of the hollow particles is 30 vol.% or more and 75 vol.% or less, and the content of the water is 30 vol.% or less. The binder resin is a urethane resin or a copolymer obtained by polymerizing at least one vinyl monomer selected from the group consisting of (meth)acrylates, styrene, vinyl acetate, diene compounds, and vinyl chloride and has a glass transition temperature of -100°C or higher and 0°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition for forming a heat insulating layer and a heat insulating member. [Background technology]

[0002] For example, Japanese Patent Application Laid-Open No. 2001-240809 discloses a composition for forming a heat insulating layer containing a binder resin, hollow particles and heat-fusible fibers as a composition for forming a heat insulating layer on building materials such as interior and exterior walls of buildings and sashes. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2001-240809 A Summary of the Invention [Problem to be solved by the invention]

[0004] With the spread of DIY and other methods, for example, the application of a heat insulating layer to aluminum sashes and the like at home is now common. In this case, it is required not only to be able to apply the heat insulating layer by simple operations, but also to be able to peel off the heat insulating layer cleanly after use, for example, during the off-season.

[0005] The present invention has been made based on the above-mentioned circumstances, and its object is to provide a composition for forming an insulation layer and an insulation member that can form an insulation layer that has excellent peelability, drying properties and insulation properties. [Means for solving the problem]

[0006] The invention made to solve the above problem is a composition for forming a heat insulating layer, which contains a binder resin, hollow particles, and water, in which the hollow particle content is 30 volume % or more and 75 volume % or less, and the water content is 30 volume % or less.

[0007] Another invention made to solve the above problem is an insulating component comprising a substrate and an insulating layer laminated directly or indirectly on the substrate, the insulating layer being formed from the above-mentioned composition for forming an insulating layer. Effect of the Invention

[0008] According to the composition for forming a heat insulating layer and the heat insulating member of the present invention, a heat insulating layer having excellent peelability, drying properties and heat insulating properties can be formed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The composition for forming a heat insulating layer and the heat insulating member of the present invention will be described in detail below.

[0010] <Composition for forming heat insulating layer> The composition for forming a heat insulating layer contains a binder resin (hereinafter also referred to as "binder resin [A]"), hollow particles (hereinafter also referred to as "hollow particles [B]"), and water (hereinafter also referred to as "water [C]"). The composition for forming a heat insulating layer may contain other components (hereinafter also simply referred to as "other components") other than the binder resin [A], the hollow particles [B], and the water [C], as necessary, within a range that does not impair the effects of the present invention.

[0011] According to the composition for forming a heat insulating layer, a heat insulating layer having excellent peelability, drying property and heat insulating property can be formed. The reason why the composition for forming a heat insulating layer has the above-mentioned constitution and thereby exhibits the above-mentioned effect is not necessarily clear, but it can be presumed, for example, as follows. In other words, by setting the content of hollow particles [B] in the composition for forming an insulating layer to 30 volume % or more and 75 volume % or less, an insulating layer with excellent peelability and insulating properties can be formed, and by setting the content of water [C] to 30 volume % or less, it is believed that the composition will have excellent drying properties.

[0012] Each component contained in the heat insulating layer forming composition will be described below.

[0013] [[A] Binder resin] [A] The binder resin is not particularly limited as long as it is a resin that dissolves or disperses in [C] water, and examples thereof include acrylic resins, polyvinyl acetate resins, ethylene / vinyl acetate resins, polyvinyl chloride resins, vinyl chloride / vinyl acetate resins, polyamide resins, cellulose acetate, cellulose butyrate, ethyl cellulose, polyvinyl alcohol, chlorinated polypropylene, urea resins, melamine resins, epoxy resins, phenolic resins, furan resins, alkyd resins, unsaturated polyester resins, silicon resins, fluorine resins, polyurethane resins, acrylic urethane resins, natural rubber, reclaimed rubber, styrene-butadiene rubber, acrylonitrile-butadiene rubber, chloroprene rubber, butyl rubber, polysulfide rubber, silicone rubber, polyurethane rubber, stereo rubber (synthetic natural rubber), ethylene propylene rubber, block copolymer rubber (SBS, SIS, SEBS, etc.), etc. The heat insulation layer forming composition may contain one or more [A] binder resins.

[0014] The binder resin [A] is preferably a copolymer obtained by polymerizing at least one vinyl monomer selected from the group consisting of (meth)acrylic acid esters, styrene, vinyl acetate, diene compounds, and vinyl chloride, or a urethane resin.

[0015] The glass transition temperature (Tg) of the binder resin [A] is preferably -100°C or more and 0°C or less. In particular, if the Tg of the binder resin [A] exceeds the upper limit, the peelability of the heat insulating layer formed by the composition for forming a heat insulating layer may deteriorate. The Tg of the binder resin [A] is a value measured by a differential scanning calorimeter ("DSC Q200" by TI Instruments Japan Co., Ltd.).

[0016] [A] The binder resin may be a commercially available product, such as "JSR SBLTX 0561" from JSR Corporation, "AE299", "AE887", and "AE872D" from E-Tech Co., Ltd., and "Superflex E-200" from Daiichi Kogyo Seiyaku Co., Ltd.

[0017] The binder resin (A) may be used in the form of an emulsion or the like in which it is dissolved or dispersed in advance in water (C).

[0018] [[B]Hollow particles] [B] Hollow particles are particles having closed voids inside the particles. The term "closed voids" refers to voids that are completely closed by the particle shell or voids that are not completely closed but are closed by the particle shell to such an extent that other components such as the binder resin [A] cannot penetrate into the voids.

[0019] According to the composition for forming a heat insulating layer, by containing the hollow particles [B], it is possible to form a heat insulating layer having closed cells.

[0020] The content of the hollow particles [B] in the composition for forming a heat insulating layer is 30 volume % or more and 75 volume % or less. By setting the content of the hollow particles [B] in the above range, a heat insulating layer having excellent peelability and heat insulating properties can be formed.

[0021] The lower limit of the content of the hollow particles [B] in the composition for forming a heat insulating layer is preferably 35% by volume, more preferably 40% by volume, and even more preferably 45% by volume. By setting the lower limit of the content of the hollow particles [B] within the above range, the heat insulating property of the heat insulating layer formed by the composition for forming a heat insulating layer can be further improved. The upper limit of the content of the hollow particles [B] is preferably 70% by volume, more preferably 65% ​​by volume, and even more preferably 60% by volume. By setting the upper limit of the content of the hollow particles [B] within the above range, the peelability of the heat insulating layer formed by the composition for forming a heat insulating layer can be further improved.

[0022] The material of the hollow particles [B] may be an organic material or an inorganic material. Examples of the organic material include synthetic resins such as acrylic resins, acrylonitrile resins, styrene resins, polyesters, polyurethanes, epoxy resins, and polyvinyl chloride resins. Examples of the inorganic material include metal oxides such as silica, alumina, titania, and zirconia, and metal halides such as magnesium fluoride. Among these, the material of the hollow particles [B] is preferably a synthetic resin, and more preferably an acrylic resin, an acrylonitrile resin, a styrene resin, polyesters, polyurethanes, epoxy resins, or polyvinyl chloride resins. The composition for forming a heat insulating layer can contain one or more types of hollow particles [B].

[0023] The lower limit of the average particle size of the hollow particles [B] is preferably 0.1 μm, more preferably 0.5 μm. The upper limit of the average particle size of the hollow particles [B] is preferably 100 μm, more preferably 50 μm. By setting the average particle size of the hollow particles [B] within the above range, the dispersion stability during blending can be improved. The average particle size of the hollow particles [B] is the volume average particle size (D50) measured by a laser diffraction method.

[0024] The lower limit of the specific gravity of the hollow particles [B] is preferably 0.01, more preferably 0.02. The upper limit of the specific gravity of the hollow particles [B] is preferably 0.5, more preferably 0.1. By setting the specific gravity of the hollow particles [B] within the above range, the heat insulation of the heat insulation layer formed by the composition for forming a heat insulation layer can be further improved. The specific gravity of the hollow particles [B] is a value measured in accordance with JIS-Z8807 (2012).

[0025] [B] The hollow particles may be commercially available products such as "Expancel 921WE40d24" from Nippon Phillite Co., Ltd. and "Microsphere F-65E" from Matsumoto Yushi Seiyaku Co., Ltd.

[0026] [[C]Water] The water (C) is used to dissolve or disperse the binder resin (A) and the hollow particles (B).

[0027] The content of water [C] in the composition for forming a heat insulating layer is 30% by volume or less. By setting the content of water [C] within the above range, a heat insulating layer having excellent drying properties can be formed.

[0028] The lower limit of the content of water [C] is preferably 5% by volume, more preferably 10% by volume. The upper limit of the content of water [C] is preferably 25% by volume. By setting the upper limit of the content of water [C] within the above range, the drying property of the heat insulating layer formed by the composition for forming a heat insulating layer can be further improved.

[0029] (Other Ingredients) Examples of other components include thickeners, defoamers, wetting agents, dispersants, organic solvents, preservatives, antifreezing agents, pigments, dyes, UV absorbers, antioxidants, light stabilizers, and rust inhibitors. The heat insulating layer forming composition may contain one or more other components. The content of the other components in the heat insulating layer forming composition may be appropriately determined depending on the type of components used.

[0030] Examples of the thickener include an alkali thickener, an association type thickener, etc. The content of the thickener in the composition for forming a heat insulating layer can be, for example, 0.01% by mass or more and 5% by mass or less.

[0031] The composition for forming a heat insulating layer can be prepared, for example, by preparing a dispersion of water [C] containing a binder resin [A], and mixing the dispersion with hollow particles [B] and other components as necessary. The lower limit of the solid content concentration of the composition for forming a heat insulating layer is preferably 10% by mass, more preferably 20% by mass. The upper limit of the solid content concentration of the composition for forming a heat insulating layer is preferably 70% by mass, more preferably 60% by mass. The "solid content" refers to components other than volatile components such as water [C] contained in the composition for forming a heat insulating layer.

[0032] The specific gravity of the composition for forming a heat insulating layer is preferably 0.2 or more and 0.6 or less. The specific gravity of the composition for forming a heat insulating layer is a value measured in accordance with JIS-Z8804 (2012).

[0033] The composition for forming a heat insulating layer is used to form a heat insulating layer. More specifically, the composition for forming a heat insulating layer is applied to a substrate and used to form a heat insulating layer on the substrate.

[0034] The substrate is not particularly limited, but examples include aluminum, stainless steel, iron, copper, galvanized iron, polypropylene (PP), polyethylene (PE), polycarbonate, acrylic, polyphenylene sulfide (PPS), acrylonitrile-styrene-butadiene (ABS), wood, concrete, asphalt, glass, tiles, bricks, paper, cardboard, and other materials used in building materials, automobiles, and packaging materials.

[0035] The method for applying the composition for forming a heat insulating layer to the substrate is not particularly limited, and examples thereof include a coating method using a spatula or roller, a method of applying the composition to the substrate by extruding the composition from a tubular container, etc. After application to the substrate, the composition may be dried at room temperature, or may be dried by heating at, for example, 40°C to 120°C.

[0036] According to the composition for forming a heat insulating layer, a heat insulating layer can be formed by a simple operation of coating a substrate. Therefore, for example, the work of forming a heat insulating layer on a building material such as an aluminum sash can be easily performed by an individual as part of a DIY project, rather than by a contractor. In addition, since the formed heat insulating layer has excellent peelability, the heat insulating layer can be easily peeled off manually even when the heat insulating layer is no longer needed due to reasons such as off-season or aging. The composition for forming a heat insulating layer is not only excellent in terms of convenience for workers, such as drying and peeling properties, but also excellent in the heat insulating properties required for a heat insulating layer.

[0037] The heat insulating layer formed by the composition for forming a heat insulating layer can maintain a high or low temperature state, and can save energy by maintaining the state. In addition, it has the effect of suppressing the influence of high or low temperature states on the surrounding environment, or preventing burns or frostbite caused by direct contact with objects in those states. For example, in winter, it is useful for preventing condensation in aluminum sashes that separate the indoor and outdoor areas with temperature differences. Specific applications include building materials for preventing condensation in aluminum sashes, insulation materials for automobiles, and also window glass, packaging materials, and packaging materials as insulating cushioning materials.

[0038] <Thermal insulation materials> The heat insulating member includes a base material and a heat insulating layer laminated directly or indirectly on the base material. The heat insulating layer is formed from the heat insulating layer forming composition described above. Therefore, the heat insulating member can be suitably used as a member that exhibits excellent heat insulating properties.

[0039] The substrate is not particularly limited, but examples include aluminum, stainless steel, iron, copper, galvanized iron, polypropylene (PP), polyethylene (PE), polycarbonate, acrylic, polyphenylene sulfide (PPS), acrylonitrile-styrene-butadiene (ABS), wood, concrete, asphalt, glass, tiles, bricks, paper, cardboard, and other materials used in building materials, automobiles, and packaging materials.

[0040] The heat insulating layer is a layer having a closed cell structure formed by the heat insulating layer forming composition. The average thickness of the heat insulating layer can be appropriately determined depending on the intended use of the heat insulating member, and can be, for example, 0.5 mm or more and 20 mm or less. The average thickness of the heat insulating layer can be appropriately adjusted by the amount of the heat insulating layer forming composition applied. The average thickness of the heat insulating layer is the average value of the thicknesses at any 10 points.

[0041] The lower limit of the specific gravity of the heat insulating layer is preferably 0.1, more preferably 0.2. The upper limit of the specific gravity of the heat insulating layer is preferably 0.5, more preferably 0.4. By setting the specific gravity of the heat insulating layer within the above range, the peelability and heat insulating property of the heat insulating layer can be further improved. EXAMPLES

[0042] The present invention will be described in detail below based on examples, but the present invention is not limited to these examples in any way.

[0043] <Preparation of composition for forming heat insulating layer> The components used in the preparation of the composition for forming a heat insulating layer are shown below.

[0044] ([A] Binder resin) (A-1): Styrene-butadiene rubber (JSR Corporation's "JSR SBLTX 0561", Tg: -63°C) (A-2): Acrylic resin (AE299 from E-Tech Co., Ltd., Tg: -60°C) (A-3): Urethane resin (Daiichi Kogyo Seiyaku Co., Ltd.'s "Superflex E-200", Tg: -38°C) (A-4): Acrylic resin (AE872D from E-Tech Co., Ltd., Tg: 15°C)

[0045] ([B] Hollow particle) (B-1): Acrylic hollow particles ("Expancel 921WE40d24" by Nippon Phillite Co., Ltd., specific gravity: 0.024, average particle size: 45 μm) (B-2): Acrylonitrile-based hollow particles ("F-65E" by Matsumoto Yushi Pharmaceutical Co., Ltd., specific gravity: 0.025, average particle size: 50 μm)

[0046] (Other Ingredients) Thickener: San Nopco Ltd.'s "SN Thickener A-812"

[0047] [Example 1] Preparation of heat insulating layer forming composition (E-1) [A] 145 parts by mass of the aqueous dispersion of (A-1) as the binder resin (containing 69 parts by mass of (A-1)) was stirred, while 299 parts by mass of (B-1) as the hollow particles [B] and 0.1 parts by mass of the thickener were added in this order to prepare a composition for forming a heat insulating layer (E-1). The solid content concentration of the composition for forming a heat insulating layer (E-1) was 30% by mass.

[0048] [Examples 2 to 7 and Comparative Examples 1 to 4] Preparation of compositions for forming heat insulation layer (E-2) to (E-7) and (CE-1) to (CE-4) Compositions for forming a heat insulating layer (E-2) to (E-7) and (CE-1) to (CE-4) were prepared in the same manner as in Example 1, except that the types and amounts of each component shown in Table 1 below were used.

[0049] In Table 1 below, the numerical values ​​in the rows of [A] binder resin, [B] hollow particles, and [C] water and thickener represent parts by mass. In Table 1 below, "-" indicates that the corresponding component was not added. For example, in the column of Example 1 in Table 1 below, the row of "water" is marked with "-". This does not mean that the heat insulating layer forming composition (E-1) does not contain water, but rather that no water was added other than the water contained in the aqueous dispersion of (A-1) when preparing (E-1).

[0050] (Measurement of specific gravity of composition for forming heat insulating layer) The specific gravity of each of the compositions for forming a heat insulating layer prepared above was measured in an atmosphere of 23° C. and 50% Rh in accordance with JIS-Z8804 (2012).

[0051] (Measurement of specific gravity of binder resin, hollow particles and heat insulating layer) The binder resin, hollow particles, and heat insulating layer were dried by heating at 40°C for 72 hours, and after thorough drying, the specific gravity was measured in an atmosphere of 23°C and 50Rh% in accordance with JIS-Z8807 (2012).

[0052] (Calculation of volume fraction of each component) The volume fractions of the binder resin [A], the hollow particles [B] and the water [C] in the composition for forming a heat insulating layer were calculated using the following formulas (1) to (3). The calculation results are also shown in Table 1 below. [A] Volume fraction of binder resin = (Wr / Dr) / (Wf / Df) (1) [B] Volume fraction of hollow particles = (Wp / Dp) / (Wf / Df) (2) [C] Volume fraction of water = (Ww / Dw) / (Wf / Df) (3)

[0053] The abbreviations used in the above formulas (1) to (3) are as follows: Wr: [A] Mass of binder resin Dr: [A] Specific gravity of binder resin Wf: Mass of the composition for forming the heat insulating layer Df: Specific gravity of the composition for forming the heat insulating layer Wp: [B] Mass of hollow particle Dp: [B] Specific gravity of hollow particles Ww: [C] Mass of water Dw: [C] Specific gravity of water (constant 1)

[0054] <Formation of heat insulating layer> A 2.7 mm thick SUS plate was placed around an aluminum substrate (A6063 with an anodized surface) of 70 mm x 150 mm. The heat insulating layer forming composition prepared above was poured into it and leveled with a spatula to the same thickness as the SUS plate. After drying for 24 hours in a 23°C, 50% Rh environment, the SUS plate was removed and a heat insulating layer was formed on the aluminum substrate. The thickness of the obtained heat insulating layer was 2 mm.

[0055] <Evaluation> The peelability, drying property and heat insulation property were evaluated according to the following methods, and the results are shown in Table 1 below.

[0056] [Peelability] The insulation layer formed above was checked to see if it could be peeled off from the aluminum substrate by pinching it with fingers. Peelability was rated as "A" (good) if it peeled off cleanly without leaving any insulation layer on the aluminum substrate surface, "B" (fairly good) if a small amount of insulation layer remained on the aluminum substrate surface but could be wiped off, and "C" (poor) if a large amount of insulation layer remained on the aluminum substrate surface.

[0057] [Drying] A 2 mm thick heat insulating layer was formed in the same manner as in the above "Formation of Heat Insulating Layer" except that the base material was release paper and the drying time was 12 hours. The heat insulating layer on the formed release paper was peeled off, and the surface of the heat insulating layer that had been in contact with the release paper (hereinafter also referred to as the "reverse side") was touched with a finger. If there was no moisture, it was rated as "A" (good); if the reverse side was slightly damp, it was rated as "B" (slightly good); and if there were water droplets remaining on the reverse side or if part of the heat insulating layer remained on the release paper, it was rated as "C" (poor).

[0058] [Thermal insulation] A 2 mm insulating layer was formed in the same manner as in the above "Formation of an insulating layer" except that the base material was release paper and the drying time was 24 hours. The insulating layer formed on the release paper was peeled off and cut into a size of 20 mm x 40 mm. The cut insulating layer was attached to the outer side of a SUS container, ice water was placed in the container, and the container was left to stand for 2 hours in an atmosphere of 23 °C and 50 RH%. If no condensation occurred on the surface of the insulating layer after 2 hours, it was evaluated as "A" (good), if a small amount of condensation occurred, it was evaluated as "B" (slightly good), and if condensation occurred, it was evaluated as "C" (bad).

[0059] [Table 1]

[0060] As is clear from the results in Table 1, the insulating layer formed using the insulating layer forming composition of the example had superior peelability, drying properties and insulation properties compared to the insulating layer formed using the insulating layer forming composition of the comparative example.

Claims

1. A binder resin; Hollow particles; Water and Contains The content of the hollow particles is 30% by volume or more and 75% by volume or less, The water content is 30% by volume or less, The glass transition temperature of the binder resin is −100° C. or higher and 0° C. or lower, The composition for forming a heat insulating layer having peelability, wherein the hollow particles are synthetic resin particles.

2. The composition for forming a heat insulating layer having peelability according to claim 1, wherein the binder resin is a copolymer obtained by polymerizing at least one vinyl monomer selected from the group consisting of (meth)acrylic acid esters, styrene, vinyl acetate, diene compounds and vinyl chloride, or a urethane-based resin.

3. 3. The composition for forming a heat insulating layer having peelability according to claim 1 or 2, wherein the hollow particles have an average particle size of 0.1 μm or more and 200 μm or less.

4. The composition for forming a heat insulating layer having peelability according to any one of claims 1 to 3, wherein the specific gravity of the hollow particles is 0.01 or more and 0.5 or less.

5. A thermal insulation member comprising a substrate and a thermal insulation layer laminated directly or indirectly on the substrate, A heat insulating member, wherein the heat insulating layer is formed from the composition for forming a heat insulating layer having peelability according to any one of claims 1 to 4.

6. The heat insulating member according to claim 5, wherein the specific gravity of the heat insulating layer is 0.1 or more and 0.5 or less.

Citation Information

Patent Citations

  • Thick film type insulating coating

    JP2000186229A

  • Coating composition for forming heat-insulating layer, molded article, and method of producing molded article

    JP2001240809A

  • Heat insulating coating material

    JP2008095031A

  • Laminate

    JP2012011707A

  • Thermal barrier-thermal insulation paint

    JP2018070697A